Pengaruh VariasiArus dan Posisi Pengelasan SMAW terhadap Sifat Mekanik Baja ST 37 - Iwan Nugraha Gusniar; Ahmad Juhri; Viktor Noubnome (Jurnal Teknik Mesin, 2021)
The purpose of this study was to determine the difference in the value of tensile strength, impact and microstructure test results on ST 37 steel plates due to variations in current strength of 80 A, 85 A and 90 A and 1G, 2G and 3G welding positions. The results of this study show the value of Max.load, current strength of 80 A 3G welding position gets the highest value of 5650 kgf, value of Tinsile strength, current strength of 80 A 3G welding position gets the highest value of 44.78 (kgf/mm2), then the strain value, the current strength of 80 A for the 3G welding position gets the highest value of 0.9% and the value of the modulus of elasticity, the current strength of 80 A for the 3G welding position gets the highest value of 97.94 (GPa,KN/mm2), In the value of the impact test results, the current strength of 80 A is the 1G welding position that gets the highest value, which is 116 Joules. In the observation of microstructure testing, 3 points were carried out, Weld metal, HAZ and Base metal at each strong current